2010
DOI: 10.1371/journal.ppat.1000719
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Proteome and Lipidome Profiles Reveal Hepatitis C Virus-Associated Reprogramming of Hepatocellular Metabolism and Bioenergetics

Abstract: Proteomic and lipidomic profiling was performed over a time course of acute hepatitis C virus (HCV) infection in cultured Huh-7.5 cells to gain new insights into the intracellular processes influenced by this virus. Our proteomic data suggest that HCV induces early perturbations in glycolysis, the pentose phosphate pathway, and the citric acid cycle, which favor host biosynthetic activities supporting viral replication and propagation. This is followed by a compensatory shift in metabolism aimed at maintaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
422
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 374 publications
(446 citation statements)
references
References 67 publications
20
422
2
2
Order By: Relevance
“…Although DENV and polioviruses stimulate PC synthesis (17,20), it is not clear whether HCV infection increases total PC levels. Nevertheless, certain PC species, such as PC 30:0, increased significantly, whereas some decreased (e.g., PC 35:1) upon HCV infection (35). To determine if the enhanced synthesis/accumulation of PC at the site of viral replication is a common feature associated with (+)RNA virus infections, we checked distribution and signal intensity of PC and PE in cells infected with DENV, HCV, or poliovirus.…”
Section: Virus-stimulated and Viral Replication Site-localized Pc Accmentioning
confidence: 99%
“…Although DENV and polioviruses stimulate PC synthesis (17,20), it is not clear whether HCV infection increases total PC levels. Nevertheless, certain PC species, such as PC 30:0, increased significantly, whereas some decreased (e.g., PC 35:1) upon HCV infection (35). To determine if the enhanced synthesis/accumulation of PC at the site of viral replication is a common feature associated with (+)RNA virus infections, we checked distribution and signal intensity of PC and PE in cells infected with DENV, HCV, or poliovirus.…”
Section: Virus-stimulated and Viral Replication Site-localized Pc Accmentioning
confidence: 99%
“…Indeed, recent studies based on transcriptome and proteomic analyses have demonstrated that expression of host genes involved in the biosynthesis, degradation and transport of intracellular lipids is profoundly altered upon infection. [86][87][88][89] The expression of SREBPs, which control transcription of genes required for cholesterol biosynthesis, 90 is stimulated both by HCV infection and It was demonstrated that NS proteins associate with cholesterol-rich lipid rafts and that depletion of cholesterol with statins selectively reduces HCV RNA replication. 104 However, statins are inhibitors of the mevalonate pathway, 99 which produces not only cholesterol, but also non-sterol isoprenoids, including geranylgeranyl and farnesyl.…”
Section: Role Of Lipid Metabolism In Hcv Rna Replicationmentioning
confidence: 99%
“…Although the significance of this simultaneous induction in lipid anabolism and catabolism remains unclear, the authors argue that β-oxidation may help to maintain elevated ATP levels to support energy-dependent biosynthetic processes as well as to limit the accumulation and toxic effect of ceramide overload. 86 In the last years, the role of cholesterol in HCV infection has gained much attention. In mammalian cells, cholesterol can be either synthesized via the mevalonate pathway, 99 or generated by internalization and degradation of LDL particles.…”
Section: Role Of Lipid Metabolism In Hcv Rna Replicationmentioning
confidence: 99%
“…sterol biosynthesis, fatty acid metabolism and synthesis of specific phosphoinositides [15]. For instance, a marked alteration of cellular metabolism and an increase in fatty acid biosynthetic pathway have been described upon human cytomegalovirus (HCMV), DENV or HCV infection [1, 5,6,11]. The association of viral multiplication with modulation of host cell factors involved in lipid metabolism is not an exclusive feature of animal viruses, thus, replication and recombination of the plant pathogens tombusviruses has been revealed to rely on host genes involved in lipid metabolism [96][97][98][99].…”
Section: Cellular Lipids Involved In Viral Replication Complex Assemblymentioning
confidence: 99%
“…The involvement of lipids in the infectious cycle is shared by enveloped viruses (those viruses whose infectious particle is wrapped by one or more lipid membranes) and non-enveloped viruses [1][2][3][4]. Apart from taking advantage on cellular lipids that are usually located inside cells, viruses induce global metabolic changes on infected cells, leading to the rearrangement of the lipid metabolism to facilitate viral multiplication [1, [5][6][7][8][9][10][11]. In some cases, these alterations produce the reorganization of intracellular membranes of the host cell, building the adequate microenvironment for viral replication [12,13].…”
Section: Introductionmentioning
confidence: 99%